2012
DOI: 10.1017/s0032247412000071
|View full text |Cite
|
Sign up to set email alerts
|

Highly skilled migration in the urban Arctic: a Norwegian case study on skilled migrant labour market integration

Abstract: Arctic Norway is a region with a shortage of highly skilled professionals and international expertise, in many work sectors. Fast growing cites attract people from other regions and also high skilled migrants. It is a paradox that skilled migrants often fail to get qualified work in the local labour market. To understand this and to capture the complexity of labour market participation, this article draws on interviews with recruitment agencies and highly skilled migrants, attending a recruitment programme ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
(10 reference statements)
3
12
0
Order By: Relevance
“…Accordingly, adults are often motivated to learn due to a problem, issue, or challenge they face personally or professionally. One salient problem that motivates high-skilled female immigrants -based on findings from this study and previous literature -is the status collapse they experience in their careers upon migrating to a new land (Chiswick et al, 2005;Fossland, 2012;Liversage, 2009;Ramboarison-Lalao et al, 2012). Our results show that those immigrants who perceive a status collapse to be problematic to their self-concept proactively set the learning cycle in motion.…”
Section: An Experiential Learning Model Of Career Reconstruction Amonsupporting
confidence: 63%
See 1 more Smart Citation
“…Accordingly, adults are often motivated to learn due to a problem, issue, or challenge they face personally or professionally. One salient problem that motivates high-skilled female immigrants -based on findings from this study and previous literature -is the status collapse they experience in their careers upon migrating to a new land (Chiswick et al, 2005;Fossland, 2012;Liversage, 2009;Ramboarison-Lalao et al, 2012). Our results show that those immigrants who perceive a status collapse to be problematic to their self-concept proactively set the learning cycle in motion.…”
Section: An Experiential Learning Model Of Career Reconstruction Amonsupporting
confidence: 63%
“…To recap, our study revealed that most females had a non-linear entry in the job market, first going through a period of occupational status collapse, which gave them the initial motivation to activate the learning cycle. While previous studies on the career development of skilled migrants similarly reported on the status drop immediately after migration, talent waste, and downward career mobility (Chiswick et al, 2005;Fossland, 2012;Ressia et al, 2017;Liversage, 2009), we theoretically construed this status collapse as the primary push that drives skilled immigrants, triggering the experiential learning cycle. Perceptions of status collapse that trigger the learning cycle is especially salient and problematic among career-oriented immigrants whose core self-identities are strongly tied to their careers.…”
Section: S Why I Accepted It the Way It Is I Can't Change It"mentioning
confidence: 96%
“…Brain waste, meaning that the migrant's education is not approved, and they end up in the secondary labour market, despite being qualified for jobs in the primary market is also a topic of concern (Fossland (2012(Fossland ( , 2013. In Fossland's study interviewing representatives of temporary employment agencies', they reported that employers do not appreciate and value the skills and education of their migrant employees (2012).…”
Section: A Voluntary or Involuntary Choicementioning
confidence: 99%
“…In order to meet their clients' expectations (employers) the temporary agencies play a major role in mediating the 'right type of workers'. This is a process in which they contribute in shaping the human capital of the migrants by changing their behaviour in direction of a normative expectation of 'the good worker' (Findlay, McCollum, Shubin, Apsite, & Krisjane, 2013, Fossland, 2012. Therefore, the agencies' role goes beyond mediating.…”
Section: A Triangular Partnershipmentioning
confidence: 99%
See 1 more Smart Citation